Green Innovation and Economic Growth in a North-South Model - Witajewski-Baltvilks, Jan (World Bank, Washington, DC, 2022)
If one region of the world switches its research effort from dirty to clean technologies, will other regions follow To investigate this question, this paper builds a North-South model that combines insights from directed technological change and quality-ladder endogenous growth models with business-stealing innovations. While North represents the region with climate ambitions, both regions have researchers choosing between clean and dirty applications, and the resulting technologies are traded. Three main results emerge: (i) In the long-run, if North's research and development (R&D) sector is large enough, researchers in South will follow the switch from dirty to clean R&D in North, motivated by the growing value of clean markets. (ii) If the two regions direct research effort toward different sectors and the outputs of the two sectors are gross substitutes, then the long-run growth rates in both regions are lower than if the global research effort were invested in one sector. (iii) If North's government induces its researchers to switch to clean R&D through clean technology subsidies, the welfare-maximizing choice for South is to ensure that all of its researchers switch too, unless the social discount rate is high. The last result is true even if South's R&D sector is large.